A Visible‐Light Driven Photoelectrochemical Aptasensor for Endocrine Disrupting Chemicals Bisphenol A with High Sensitivity and Specificity. Issue 7 (11th June 2013) - Zhang, Yingying; Cao, Tongcheng; Huang, Xiaofeng; Liu, Meichuan; Shi, Huijie; Zhao, Guohua
Abstract A visible‐light driven photoelectrochemical (PEC) sensor based on aptamer immobilized TiO2‐Fe2O3 nanotubes was proposed for the first time and highly sensitive and selective bisphenol A determination was realized. Taking advantage of the alloy oxide nanotube structure, high surface area, good biocompatibility, superior photoelectrocatalytic performance, a limit of detection toward BPA as low as 1.8×10−11 M with linearity in the range from 1.8×10−11 to 3.2×10−9 M could be achieved. Specificity was greatly exhibited for this aptasensor under 100‐fold excess concentration of estriol, resorcinol, nonylphenol, 2, 4‐D, acetamiprid, chlorpyrifos and omethoate. Simultaneously, satisfactory results were obtained in real water sample investigation from industrial plastics and drinking water. A novel visible‐light driven PEC method for highly sensitive and selective detection of BPA was thus established.